Practical cyber intelligence how action-based intelligence can be an effective response to incidents - Bautista, Wilson (Packt Publishing, 2018)
Cyber intelligence is the missing link between your cyber defense operation teams, threat intelligence, and IT operations to provide your organization with a full spectrum of defensive capabilities. This book kicks off with the need for cyber intelligence and why it is required in terms of a defensive framework.